HUBUNGAN STATUS SOSIAL EKONOMI ORANGTUA DENGAN MOTIVASI BELAJAR PADA MAHASISWA ANGKATAN 2013 FAKULTAS KEDOKTERAN UNIVERSITAS SAM RATULANGI - Karouw, Caroline R.M.; Opod, Henry; Sinolungan, Jehosua S.V. (Universitas Sam Ratulangi, 2015)
Abstract: Learning is a process that can not be separated from human life. Psychic impulse to learn is the motivation to learn. In the learning process, parents are among the factors that have a role. This study aims to determine the relationship of socio-economic status of parents with students' learning motivation. Data were collected through questionnaires. The results showed there was no correlation between socio-economic status of parents with learning motivation of Medicine Faculty Sam Ratulangi University class of 2013 students p = 0.444 (p > 0.05) and the correlation value is -0.062. It can be concluded that there was no correlation between socioeconomic status of parents with students’ learning motivation.Keywords: socio-economic status, learning motivationAbstrak : Belajar merupakan proses yang tidak dapat dipisahkan dari kehidupan manusia,, Dorongan psikis dalam diri untuk belajar merupakan motivasi belajar. Dalam proses belajar, orangtua merupakan salah satu faktor yang memiliki peran. Penelitian ini bertujuan untuk mengetahui hubungan status sosial ekonomi orangtua dengan motivasi belajar mahasiswa. Pengambilan data melalui kuesioner. Hasil penelitian menunjukkan tidak ada hubungan antara status sosial ekonomi orangtua dengan motivasi belajar mahasiswa angkatan 2013 Fakultas Kedokteran Universitas Sam Ratulangi p=0,444 (p > 0,05) dan nilai korelasi sebesar -0,062. Dapat disimpulkan bahwa tidak terdapat hubungan antara status sosial ekonomi orangtua dengan motivasi belajar mahasiswa.Kata kunci: Status sosial ekonomi, motivasi belajar